Simulation and experiment study of optimizational PID control with changing integration rate - Hou Tao; Hong-xia Niu; Fan Duo-wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper is to demonstrate an optimizational PID control with changing integration rate approach, and it was validated and researched by applying to the two-linked tanks system. Analyzed the control principle of variable integral PID in this research, and optimized the variable function of variable integral PID control to improve the design.Deduced the improved variable integral PID control algorithm,and it was applied to the two-linked tanks system. And then made a simulation system and application experiment in the advanced process control experimental apparatus to value it. The results show that the optimizational variable integral PID control enables the system to improve the rapidity,stationarity and accuracy, also shows that the correctness and superiority of the control method. It really an useful method to provide a advanced way for the control system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1808